Tempo de cérebro - Ribeiro, Sidarta (Estudos Avançados, 2013)
The neurosciences are at the confluence of mathematics, physics, chemistry, biology, psychology, philosophy, and the arts. They fascinate the general public due to the possibility of understanding the mechanisms of emotions, thoughts and actions, disease and madness, learning and forgetting, dreams and imagination, phenomena that define and conform us. How to interpret the new findings in neuroscience? This article discusses some topics of broad social interest: aging, education, drugs, the scientific return to psychoanalysis and the problem of consciousness.